2005
DOI: 10.1021/om050128v
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Cp2Zr-, (MeO)2Zr-, and M(PH3)-Mediated Coupling Reactions of Acetylenes (M = Ni, Pt). Significant Differences between Early- and Late-Transition-Metal Complexes

Abstract: Theoretical calculations with DFT, MP2 to MP4(SDQ), and CCSD(T) methods clearly display that the Cp 2 Zr-mediated coupling reaction of two acetylene molecules easily takes place through a nonsymmetrical transition state with nearly no barrier and significantly large exothermicity but the M(PH 3 )-mediated reaction (M ) Ni, Pt) takes place through a symmetrical transition state with either a considerably large activation barrier for M ) Pt or a moderately large activation barrier for M ) Ni. The charge-transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 98 publications
1
18
0
Order By: Relevance
“…Much more works concentrate on the determining the structures of the LE and ICT states,4–9 while the precise nature of the difference between the properties of the electronically excited state in protic and aprotic solvents is little understood. Hydrogen bonding in protic solvents can lead to complicated interactions, and thus may significantly influence the ICT state for DMABN in the protic solvents 10–65. Kowk et al have demonstrated and monitored the formation of a hydrogen‐bonded ICT state for the photoexcited DMABN in the protic solvent methanol (MeOH) using the time‐resolved infrared (TRIR) absorption spectra 61–63.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much more works concentrate on the determining the structures of the LE and ICT states,4–9 while the precise nature of the difference between the properties of the electronically excited state in protic and aprotic solvents is little understood. Hydrogen bonding in protic solvents can lead to complicated interactions, and thus may significantly influence the ICT state for DMABN in the protic solvents 10–65. Kowk et al have demonstrated and monitored the formation of a hydrogen‐bonded ICT state for the photoexcited DMABN in the protic solvent methanol (MeOH) using the time‐resolved infrared (TRIR) absorption spectra 61–63.…”
Section: Introductionmentioning
confidence: 99%
“…However, some weak interactions in many molecular systems have been described by DFT or TDDFT methods with comparable accuracy to the higher level. Sakaki et al have extensively investigated the intramolecular and intermolecular weak interactions as well as the bonding nature of the transition metal‐silylene complexes with DFT and other high‐level methods 51–56. Sobolewski and Domcke have perfectly studied the intramolecular and intermolecular hydrogen bonding in both the ground state and electronically excited states using the DFT and TDDFT methods 33, 40–45…”
Section: Introductionmentioning
confidence: 99%
“…Metallacyclopentadiene complexes of transition metals have been extensively investigated as key intermediates in various catalytic reactions, such as cyclotrimerization of three alkynes and co-cyclotrimerization of two alkynes with nitriles and heterocumulenes, for the production of aromatic and heteroaromatic compounds. In addition, application as synthetically useful reagents for some stoichiometric reactions is demonstrated for the reaction with sulfur sources, main group element halides, and halogen sources for constructing five-membered heterocycles, 1,4-dihalo-1,3-butadienes, diene-based polymers, and so on. Metallacyclopentadienes of late transition metals can be generated by concerted oxidative cyclization of two alkynes at low-valent metal centers, while the formation of metallacyclopentadiene of early transition metals proceeds in a stepwise mechanism through the initial generation of η 2 -alkyne complexes followed by insertion of the second alkyne . Notably, retro-oxidative cyclization via C β –C β bond fission is observed for some early transition metal complexes upon introducing bulky substituents at the α-position of the metallacyclopentadienes, producing the isomerized metallacyclopentadiene with bulky substituents at the β-position via the η 2 -alkyne complex …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some weak interactions in many molecular systems have been described by DFT or TDDFT methods with comparable accuracy to the higher level 74–76. Sakaki and coworkers have excellently investigated the intramolecular and intermolecular weak interactions as well as the bonding nature of the transition metal‐silylene complexes with DFT and other high‐level methods 77–82…”
Section: Introductionmentioning
confidence: 99%